Talent transformation of seafarers in the maritime industry - Ow Yong, Shirlene Jeng Yi (Nanyang Technological University, 2022)
A resilient seafaring community is essential to facilitate the maritime transportation of goods. The roles of seafarers will evolve, and new skills are required with the increased automation and digitalization of ships brought about by Industry 4.0. However, there is insufficient research to identify the exact skills needed by seafarers and how maritime education and training (MET) for seafarers should be developed. The International Convention on Standards of Training, Certification and Watchkeeping for Seafarers (STCW), the basis of MET for seafarers, has been identified as being insufficient in its current form and unlikely to meet future requirements. The gap will widen further with increasingly advanced and automated ships. This paper aims to reduce the gap between the current seafarers’ skills, mainly based on STCW requirements and new skills required. Interviews and surveys were conducted to understand skills required for seafarers from various stakeholders, initiatives for such skills acquisition, and to assess the readiness of the maritime industry in preparing seafarers for the future. Based on the study, seafarers will require three main skill sets: digitalization and technology, soft skills, and technical competencies. Seafarers will need to receive training to safely operate advanced ships. There is also a lack of awareness amongst seafarers and current seafaring students about Industry 4.0. The study also confirms the gap between the skills required by the maritime industry and the skills seafarers possess. The conclusion is that the maritime industry is not prepared for the future. Among the recommendations are raising awareness of Industry 4.0, improving collaboration among maritime stakeholders, transforming the maritime training environment to be more engaging and immersive, and introducing new courses to the MET curriculum. Hence, this paper is critical in addressing the need for talent transformation in the maritime industry to ensure that seafarers are prepared and trained in competencies for the future.